Analysis of Trail Running Tourism Potential in Mount Tampomas, Sumedang: An MSP+DM Framework Approach - Giwangkara Syaputra; Rizal Ahmad Fauzi; Adang Sudrazat (Journal Coaching Education Sports, 2026)
Sumedang Regency, particularly the Mount Tampomas area, has strong potential to be developed as a trail running tourism destination. This study aims to analyze the development potential of trail running tourism in Sumedang using the MSP+DM framework (Marketability, Sustainability, Participatory, and Disaster Mitigation). A qualitative phenomenological approach was employed through field observations, in-depth interviews, and document analysis involving tourism managers, government representatives, and local community members. Data were analyzed using NVivo 12 software. The findings show that Mount Tampomas offers significant tourism potential supported by distinctive trail characteristics, accessible transportation, and active digital promotion through social media platforms. Community participation was identified as a major supporting factor, particularly in tourism operations, environmental conservation, and emergency response activities. Sustainability practices have been implemented through standard operating procedures, environmental maintenance programs, and local economic empowerment initiatives. In the disaster mitigation aspect, the main risks identified were lightning strikes and falling trees rather than landslides, indicating a discrepancy between governmental risk assumptions and empirical field conditions. The novelty of this study lies in the integrated application of the MSP+DM framework for analyzing trail running tourism development and in highlighting differences between policy-based risk perceptions and local experiential knowledge. The study recommends strengthening integrated tourism management, visitor carrying-capacity regulations, and collaborative stakeholder involvement to support sustainable trail running tourism development in Sumedang.